2022
DOI: 10.1080/15374416.2022.2140433
|View full text |Cite
|
Sign up to set email alerts
|

Transgender-Specific Adolescent Mental Health Provider Availability is Substantially Lower in States with More Restrictive Policies

Abstract: Objective: Transgender adolescents experience adversity accessing mental healthcare, which is exacerbated by transgender-specific mental health provider shortages in the United States.Factors associated with variability in transgender-specific mental health provider availability across states-especially at the macro-social level-have yet to be identified, hindering efforts to address these shortages. To remedy this gap, we queried whether transgender-specific adolescent mental health provider availability vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The passage of additional transphobic laws/policies in these states may result in even higher rates of psychological distress and suicidality among transgender residents. This possibility is particularly concerning considering emerging evidence that transgender individuals’ access to supportive mental healthcare is substantially lower in states with higher levels of structural transphobia [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The passage of additional transphobic laws/policies in these states may result in even higher rates of psychological distress and suicidality among transgender residents. This possibility is particularly concerning considering emerging evidence that transgender individuals’ access to supportive mental healthcare is substantially lower in states with higher levels of structural transphobia [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, to demonstrate that these associations were not better explained by other features of the social environment, we controlled for state-level income inequality (i.e., the Gini coefficient) [ 57 ] and religiosity (i.e., the percent of Evangelical Christians and Latter-day Saints/Mormons in each state) [ 58 ]. The religiosity measure has been used as a covariate in similar structural stigma studies [ 59 , 60 ], including a recent study with transgender youth [ 46 ], as past research indicates that members of these two religions endorse more negative attitudes toward transgender people and their rights compared to members of other religions [ 61 , 62 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A. Price, Weisz, et al, 2022) and access (Hollinsaid et al, 2022;Roulston et al, 2022) for stigmatized youth (see Figure 1). The present paper provides a brief overview of the scientific literature on structural stigma and youth mental health treatment, and details three future research directions we hope readers pursue.…”
Section: Future Directions In Mental Health Treatment With Stigmatize...mentioning
confidence: 99%
“…In a large sample of sexual minority youth of Color, found that structural homophobia and racism were strongly associated with treatment access, such that sexual minority youth of Color living in states with more homophobic and racist attitudes reported being less likely to access treatment, even when controlling for mental health provider availability. Likewise, Hollinsaid et al (2022) documented substantially lower rates of mental health providers who specialize in providing services to transgender youth in states with more transphobic laws/policies while controlling for other state-level factors, such as political and religious conservatism. Similar studies have also identified a dearth of genderaffirming assessment materials (e.g., inclusive online intake forms; Holt et al, 2019Holt et al, , 2021, fewer referrals for gender-affirming services for transgender youth (Indremo et al, 2022), and less affirming services for sexual minority and transgender young people (Campbell & Mena, 2021) in places with high levels of structural stigma.…”
Section: Structural Stigma and Mental Health Treatment Efficacy And A...mentioning
confidence: 99%